Wind load effect on the lateral instability of precast beams on elastomeric bearing supports - CARDOSO,M. T. S. A. (2020)
Abstract The behavior of slender precast beams related to lateral stability in the transitional and in service phases is worrying. The presence of geometric imperfections aggravates and makes the problems of instability more susceptible. The main objective of this work is to evaluate the behavior of concrete beams on elastomeric bearings and to analyze the influence of variables such as: concrete strength, wind load and bearing compression stiffness. For the numerical nonlinear analysis the software ANSYS based on the Finite Element Method was used. The analyses show that the influence of the strength of the concrete is significant in the lateral stability of the beam. The wind load represents a considerable decrease in the contact (lift off) between the beam and the bearing. Finally, the combination of these factors can result in a critical stress situation in the beam, and it is not possible to have equilibrium, causing its toppling.